2021
DOI: 10.1038/s41467-021-26528-w
|View full text |Cite
|
Sign up to set email alerts
|

A reasonable approach for the generation of hollow icosahedral kernels in metal nanoclusters

Abstract: Although the hollow icosahedral M12 kernel has been extensively observed in metal nanoclusters, its origin remains a mystery. Here we report a reasonable avenue for the generation of the hollow icosahedron: the kernel collapse from several small nano-building blocks to an integrated hollow icosahedron. On the basis of the Au alloying processes from Ag28Cu12(SR)24 to the template-maintained AuxAg28-xCu12(SR)24 and then to the template-transformed Au12CuyAg32-y(SR)30, the kernel evolution/collapse from “tetrahed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…As a note, in a recent study, Kang et al reported a shortening of the A3-coupling reaction time from hours to minutes at higher temperatures (175 °C) catalyzed by a thermally robust, trimetallic Au 1 Ag 16 Cu 12 (SSR) 12 (PPh 3 ) 4 NC (SSR: benzene-1,3-dithiolate), demonstrating the unique potential of trimetallic alloying in catalytic enhancement. 35 By using a chiral reducing agent, Hakkinen and Zheng groups reported a novel phosphine and thiolate ligand co-protected trimetallic [Au 7 Ag 6 Cu 2 (R- or S-BINAP) 3 (SCH 2 Ph) 6 ]SbF 6 (BINAP: 2,2′-bis(diphenylphosphino)-1,1′-binaphthyl) NC with tertiary chiral nanostructure. 36 In this study, Au 2 Ag 8 Cu 5 is the first case of all-alkynyl-protected trimetallic superatom documented so far.…”
Section: Introductionmentioning
confidence: 99%
“…As a note, in a recent study, Kang et al reported a shortening of the A3-coupling reaction time from hours to minutes at higher temperatures (175 °C) catalyzed by a thermally robust, trimetallic Au 1 Ag 16 Cu 12 (SSR) 12 (PPh 3 ) 4 NC (SSR: benzene-1,3-dithiolate), demonstrating the unique potential of trimetallic alloying in catalytic enhancement. 35 By using a chiral reducing agent, Hakkinen and Zheng groups reported a novel phosphine and thiolate ligand co-protected trimetallic [Au 7 Ag 6 Cu 2 (R- or S-BINAP) 3 (SCH 2 Ph) 6 ]SbF 6 (BINAP: 2,2′-bis(diphenylphosphino)-1,1′-binaphthyl) NC with tertiary chiral nanostructure. 36 In this study, Au 2 Ag 8 Cu 5 is the first case of all-alkynyl-protected trimetallic superatom documented so far.…”
Section: Introductionmentioning
confidence: 99%
“…In this quest, atomically precise Au nanoclusters have attracted intensive interest because they possess high molecular purity, well-defined structures, and high surface-to-volume ratios and have been studied as ideal model systems for understanding catalytic properties at the atomic level. In particular, a series of thiolate-protected Au nanoclusters have been studied for CO 2 RR, although the detailed catalytic mechanisms are not well understood and are controversial. , …”
mentioning
confidence: 99%
“…10,[40][41][42] For example, many studies have shown that the structural configurations of nanoclusters protected by alkynes, 43,44 carboxylic acids, 45,46 or halogens 47,48 differ from those of the thiolate-protected ones, even they have the same number of metal atoms and similar metal-ligand binding modes. [49][50][51][52][53][54][55][56][57] However, precise structural manipulation of a specific site in nanoclusters is still difficult to achieve by merely changing the type of ligand. In contrast with the aforementioned covalent ligands, phosphines, as coordination ligands, are considered as candidates for regulating or altering the local structure of a certain nanocluster.…”
Section: Introductionmentioning
confidence: 99%